UPACARA KEMATIAN SAUR MATUA BATAK TOBA: ANALISIS TRADISI LISAN - Relly Monika Hasugian (Center of Language and Cultural Studies, 2017)
This study reports funeral ceremony tradition of Saur Matua of Batak Toba, Indonesia. Oral tradition is the traditional delivered orally using words, transformed by the times and the adjustment to the context of the times. A qualitative using ethnograpic approach is used in this study. Data were explored from an observation and an in-depth interview on the conduct of Saur Matua ceremony. The study revealed that Saur Matua in Toba Batak has 10 full characteristics of oral tradition: (1) Representing the events as the context; (2) Having a cultural activity; (3) To be observed and watched; (4) Traditional characteristics; (5) Inherited from generation to generation; (6) Delivering process